Enhancing Learning Autonomy through Heutagogical Flipped Learning: A Three-Semester Longitudinal Study in Indonesian Higher Education - Nurhajarurahmah, St. Zulaiha (Yayasan Pendidikan Bima Berilmu, 2025)
This study aims to analyze the effect of implementing Heutagogical Flipped Learning (HFL) on students’ learning autonomy in Indonesian higher education. The research employed a quasi-experimental longitudinal approach with a one-group pretest–posttest design, conducted over three consecutive semesters in the same course within a postgraduate mathematics education program. A total of 93 students as participated in the study. The research instruments consisted of the HFL Implementation Scale and the Learning Autonomy Scale, each comprising 20 items with content validity (Aiken’s V) ranging from 0.84 to 0.94 and reliability coefficients (α) above 0.88. Data were analyzed using descriptive statistics, paired-sample t-tests, simple linear regression, and thematic analysis of reflective interview data. The findings revealed that the implementation of HFL had a positive and significant effect on improving students’ learning autonomy, with an R² value of 0.46 (p < 0.001). The learning effect increased from a medium to a large level across semesters (Cohen’s d = 0.49 → 0.91). The longitudinal trend analysis showed an average increase of 0.22 points in learning autonomy per semester. The interview results supported the quantitative findings, showing that 83% of students expressed satisfaction with the learning process, particularly regarding learning flexibility, responsibility, and peer collaboration, although some faced technical and time-management challenges. Overall, this study confirms that HFL is effective in enhancing students’ learning autonomy and satisfaction in higher education. Its sustained implementation has the potential to foster a culture of self-directed and reflective learning aligned with Indonesia’s digital education transformation agenda.